Perancangan Sistem Informasi Rawat Jalan Pasien Di BP & RB XYZ Dengan Metodologi Berorientasi Objek - Ahmaddul Hadi (ISB Atma Luhur, 2014)
The development of information technology very quickly and proved instrumental in a variety of activities, thus supporting the performance improvement of efficiency, effectiveness and productivity for various agencies, both agencies embodiment developed and prosperous society. Health sector is one of the important sectors of the government is one sector with huge potential for development can be integrated with the presence of information technology. BP RB Hospital XYZ which became one health care center in . BP RB Hospital XYZ is one health authority that is being developed. With a considerable number of patients, lead to problems in getting information about their patients, number of patients, number of visits, total revenues, drug inventory data and drug data that has been used by the hospital. Besides the issue of data collection and archiving of patient medical records is an important thing to note. By looking at existing problems, the BP RB Hospital XYZ , with the rapid development of information technology and by utilizing information technology, it is necessary to create an application that can overcome the problems encountered so as to improve health services in order to realize the vision of the society and mission Hospital BP RB XYZ.